Morbidity and mortality in Danio rerio and Pimephales promelas exposed to antilipidemic drug mixtures (fibrates and statins) during embryogenesis: Comprehensive assessment via ante and post mortem endpoints. (January 2021) - Kingcade, A.; Ahuja, N.; Jefferson, A.; Schaffer, P.A.; Ryschon, H.; Cadmus, P.; Garrity, D.; Ramsdell, H.
Abstract: Antilipidemic drugs are routinely detected in effluent and surface waters downstream of wastewater treatment plants. A mixture exposure study with nine environmentally relevant antilipidemic drugs was performed with zebrafish ( Danio rerio, ZF) and fathead minnow ( Pimephales promelas, FHM) embryos to investigate the effects on sensitive embryologic stages. Zebrafish embryos were exposed nominally to: (a) 0.005 μM, (b) 0.05 μM, or (c) 0.5 μM of each drug in the mixture. Fathead minnow embryos were exposed nominally to: (a) 0.0005 μM, (b) 0.005 μM, or (c) 0.05 μM of each drug in the mixture. Several of the individual drug concentrations were within ranges previously found in the environment. Multiple metrics demonstrate that (a) exposure of ZF and FHM embryos to antilipidemic drugs during embryonic development results in lethal and sublethal effects, (b) ZF were more sensitive than FHM based on median lethal concentration (LC50 0.02 μM and 0.05 μM, respectively), but FHM exhibited more severe abnormal sublethal morphologies than zebrafish embryos, and (c) the sublethal effects differed between the two species. This model identified novel specific endpoints for assessing sensitive, sublethal effects of pharmaceuticals in the environment. Abnormal myofiber birefringence pattern, hemorrhage, and heart rate are not included in standard evaluations but each of these metrics demonstrated a dose-dependent response in this study. Results demonstrate risk to fish development with potential repercussions at the population level, especially if environmental concentrations increase. Highlights: Antilipidemic exposure caused lethal and sublethal effects in fish embryos. Zebrafish embryos had lower median lethal concentration than fathead minnow embryos. Fathead minnow embryos exhibit more severe abnormal morphologies than zebrafish. Sublethal effects differed between the two species. Antilipidemics may pose a significant threat to aquatic wildlife inhabiting contaminated ecosystems.